An Improved Measure of Cognitive Salience in Free Listing Tasks: A Marshallese Example. Issue 4 (November 2017) - Robbins, Michael C.; Nolan, Justin M.; Chen, Diana
A new free-list measure of cognitive salience, B ′, is presented, which includes both list position and list frequency. It surpasses other extant measures by being normed to vary between a maximum of 1 and a minimum of 0, thereby making it useful for comparisons irrespective of list length or number of respondents. An illustration of its properties, uses, and computation is provided with the aid of examples drawn from free lists of foods elicited from a sample of migrants from the Republic of the Marshall Islands.